Towards net zero food systems' at the 2023 Bonn Climate Conference - CGIAR Initiative on Low-Emission Food Systems (2023)
At the 2023 Bonn Climate Conference, the CGIAR Initiative on Low-Emission Food Systems organized a side event titled “Towards net zero food systems: how can low emission development strategies help achieve food security and economic growth?”